Advancement of TDR technique for locating power cable insulation degradation - Kuan T.M.; Ariffin A.M.; Sedau M.M.B. (Insight Society, 2023)
This paper discusses the advancement of time domain reflectometry (TDR) technique for locating degradation in power cable insulation with and without jointing. TDR technique is commonly used for localizing processes in various fields. It applies the concept of radar where a signal propagates through a medium will be reflected when there is an impedance mismatch. However, the application of TDR technique in power cable is still limited and its potential to pinpoint the exact location of degradation in power cables is to be ascertained. This study conducts experiments to investigate the potential of this technique in pinpointing the location of degradation in power cable with and without jointing. Experiments are conducted on un-degraded cable without any joint and followed by cable with jointing up to 2 cable joints. For experiments with jointing, the un-degraded cable is sectionalized into 2 parts, and one of the sections is replaced by a degraded cable. Experiments are repeated by sectionalizing the un-degraded cable into 3 parts, and each section is replaced with a degraded cable up to 2 sections. TDR results from all experiments are compiled and then analyzed. The results obtained from this study have proven that TDR technique is capable of identifying the degradation along a cable and at the same time pinpointing the exact location of degraded cable section.